1994
DOI: 10.1099/0022-1317-75-8-2065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a target protein of US3 protein kinase of herpes simplex virus type 2

Abstract: Herpes simplex virus type 2 (HSV-2) gene US3 has been shown to encode a serine-threonine protein kinase. In this study, we have tried to identify target proteins of the US3 protein kinase using a US3 lacZ insertion mutant of HSV-2. When permeabilized cells were labelled with [~-32p]ATP under the optimum conditions for the US3 enzyme, the most striking difference between wild-type HSV-2 strain 186-and mutant-infected cells was observed in the phosphorylation of proteins ranging in M r values from 14K to 22K. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…Purves et al (1991) demonstrated that US3-encoded PK of HSV-1 is involved in the phosphorylation ofa 30K protein encoded by UL34. Daikoku et al (1994) reported that HSV-2 US3-encoded PK may be involved in the phosphorylation of the US9-encoded tegument phosphoprotein. From our experiments we hypothesize that the decrease in virulence of US3 PK mutants may be caused by an accumulation of progeny virus in the perinuclear space of the host cells.…”
Section: Short Communicationmentioning
confidence: 99%
“…Purves et al (1991) demonstrated that US3-encoded PK of HSV-1 is involved in the phosphorylation ofa 30K protein encoded by UL34. Daikoku et al (1994) reported that HSV-2 US3-encoded PK may be involved in the phosphorylation of the US9-encoded tegument phosphoprotein. From our experiments we hypothesize that the decrease in virulence of US3 PK mutants may be caused by an accumulation of progeny virus in the perinuclear space of the host cells.…”
Section: Short Communicationmentioning
confidence: 99%
“…Although several viral proteins have been shown to be substrates for the US3 PK (Daikoku et al, 1994 ;Purves et al, 1991), there is no evidence that they are involved in blocking apoptosis. In summary, our present results strongly suggest a role for the US3 PK in blocking apoptosis in vivo, although the possible involvement of an additional mutation cannot completely be ruled out.…”
mentioning
confidence: 99%
“…It also drives the phosphorylation of the VZV ORF32 protein in VZV-infected cells (49). The targets of the VZV ORF66 protein kinase are not known, but the homologous protein kinases in alphaherpesviruses (sometimes referred to as the US3 protein kinases) seem to target multiple and varied proteins specific for each virus (5,6,38,55,62). Recent evidence has indicated that HSV-1 US3 protein kinase also prevents apo-ptosis following infection and thus may target cellular proteins (38).…”
mentioning
confidence: 99%